Molecular Genealogy of a Mongol Queen’s Family and Her Possible Kinship with Genghis Khan - Lkhagvasuren, Gavaachimed; Shin, Heejin; Lee, Si Eun; Tumen, Dashtseveg; Kim, Jae-Hyun; Kim, Kyung-Yong; Kim, Kijeong; Park, Ae Ja; Lee, Ho Woon; Kim, Mi Jin; Choi, Jaesung; Choi, Jee-Hye; et al. (PLOS ONE, 2016)
Members of the Mongol imperial family (designated the Golden family) are buried in a secret necropolis; therefore, none of their burial grounds have been found. In 2004, we first discovered 5 graves belonging to the Golden family in Tavan Tolgoi, Eastern Mongolia. To define the genealogy of the 5 bodies and the kinship among them, SNP and/or STR profiles of mitochondria, autosomes, and Y chromosomes were analyzed. Four of the 5 bodies were determined to carry the mitochondrial DNA haplogroup D4, while the fifth carried haplogroup CZ, indicating that this individual had no kinship with the others. Meanwhile, Y-SNP and Y-STR profiles indicate that the males examined belonged to the R1b-M343 haplogroup. Thus, their East Asian D4 or CZ matrilineal and West Eurasian R1b-M343 patrilineal origins reveal genealogical admixture between Caucasoid and Mongoloid ethnic groups, despite a Mongoloid physical appearance. In addition, Y chromosomal and autosomal STR profiles revealed that the four D4-carrying bodies bore the relationship of either mother and three sons or four full siblings with almost the same probability. Moreover, the geographical distribution of R1b-M343-carrying modern-day individuals demonstrates that descendants of Tavan Tolgoi bodies today live mainly in Western Eurasia, with a high frequency in the territories of the past Mongol khanates. Here, we propose that Genghis Khan and his family carried Y-haplogroup R1b-M343, which is prevalent in West Eurasia, rather than the Y-haplogroup C3c-M48, which is prevalent in Asia and which is widely accepted to be present in the family members of Genghis Khan. Additionally, Tavan Tolgoi bodies may have been the product of marriages between the lineage of Genghis Khan’s Borjigin clan and the lineage of either the Ongud or Hongirad clans, indicating that these individuals were members of Genghis Khan’s immediate family or his close relatives.